On a Continuous-Time Game with Incomplete Information - Cardaliaguet, Pierre; Rainer, Catherine (Mathematics of operations research, 2009)
For zero-sum two-player continuous-time games with integral payoff and incomplete information on one side, the authors show that the optimal strategy of the informed player can be computed through an auxiliary optimization problem over some martingale measures. The authors also characterize the optimal martingale measures and compute them explicitly in several examples.